Herd immunity and COVID-19 in Indonesia - Faizal, Imam Agus; Ariska Nugrahani, Nur (Jurnal Teknologi Laboratorium, 2020)
Herd immunity or herd effect is a phenomenon that occurs in groups of people who are resistant to disease. The purpose of conducting this research is to predict the number of cumulative cases of COVID-19 in Indonesia. Covid-19 cases in Indonesia on April 6, 2020, were 2235 cases spread in 34 Provinces. As many as 2491 cases in Indonesia, there were 192 patients recovered (including those treated, so they have natural antibodies in the end) while the total who died was 209 people. It is assumed that around 13% of the total cases have natural antibodies. This is also the case with SARS-CoV-2 and may explain why some individuals (perhaps those most recently able to recover from seasonal coronavirus infections) have asymptomatic infections. Finally, the theoretical concept of increasing herd immunity in pandemic and epidemic cases in Indonesia which aims to control COVID-19 still needs to be reviewed because it is seen from the mortality data that CFR COVID-19 is predicted to be around 8.39% of the population in Indonesia where the risk of death still available. The best alternative is to do a healthy lifestyle, social distancing, and waiting for the vaccine to be found.